2017
DOI: 10.1175/jcli-d-17-0093.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Assimilating Satellite Sea Ice Concentration and Thickness on Arctic Sea Ice Prediction in the NCEP Climate Forecast System

Abstract: Here sea ice concentration derived from the Special Sensor Microwave Imager/Sounder and thickness derived from the Soil Moisture and Ocean Salinity and CryoSat-2 satellites are assimilated in the National Centers for Environmental Prediction Climate Forecast System using a localized error subspace transform ensemble Kalman filter (LESTKF). Three ensemble-based hindcasts are conducted to examine impacts of the assimilation on Arctic sea ice prediction, including CTL (without any assimilation), LESTKF-1 (with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 54 publications
4
57
0
Order By: Relevance
“…The assimilation framework provides the environment for ensemble simulations and different ensemble‐based Kalman filters. The assimilation methodology used here is the local error‐subspace transform Kalman filter (LESTKF; Nerger et al, ), which was, for example, applied by Chen et al () for assimilating sea ice concentration and thickness. Compared to the classical EnKF (Evensen, ), the LESTKF is computationally more efficient because it directly accounts for the fact that the degrees of freedom for the assimilation are given by the ensemble size.…”
Section: Methodsmentioning
confidence: 99%
“…The assimilation framework provides the environment for ensemble simulations and different ensemble‐based Kalman filters. The assimilation methodology used here is the local error‐subspace transform Kalman filter (LESTKF; Nerger et al, ), which was, for example, applied by Chen et al () for assimilating sea ice concentration and thickness. Compared to the classical EnKF (Evensen, ), the LESTKF is computationally more efficient because it directly accounts for the fact that the degrees of freedom for the assimilation are given by the ensemble size.…”
Section: Methodsmentioning
confidence: 99%
“…For this, the Parallel Data Assimilation Framework (Nerger & Hiller, 2013; http:// pdaf.awi.de) was coupled online to MITgcm-REcoM2. The same data assimilation methodology was used in Chen et al (2017), Mu et al (2018), Pradhan et al (2019), and Goodliff et al (2019). This filter is computationally more efficient and has lower sampling error than the EnKF (Evensen, 1994).…”
Section: Data Assimilation Methodsmentioning
confidence: 99%
“…They found that the assimilation of the ice thickness has an obvious impact on the simulated sea ice fields, leading to significant reduction in the bias of the modeled ice thickness for several months. Collow et al [110] and Chen et al [111], respectively, have assimilated sea ice thickness from the Pan-Arctic Ice Ocean Modeling and Assimilation System (PIOMAS, an Arctic sea ice reanalysis [112]) and the combined CryoSat2 and SMOS retrievals, in the NCEP Climate Forecast System. The results showed that the experiment assimilating ice thickness results in a significant reduction of systematic bias in the forecasted ice thickness relative to the experiment assimilating ice concentration only or without sea ice assimilation.…”
Section: Sea Ice Thicknessmentioning
confidence: 99%